a SOCIALIZATION OF PHYSICAL FITNESS TESTS & MEASUREMENT EARLY AGE FOOTBALL PLAYER AT SCHOOL BANGKALAN REGENCY FOOTBALL - Widodo, Haryo Mukti (Journal of Sport Moovera (JSM), 2023)
The dissemination of tests and measurements of the physical fitness of early football players is very important as one of the supporters of a structured and programmed long-term football coaching system. This is important to maintain how the physical fitness of a soccer player can be maintained until the age of his peak. The socialization of tests and measurements of physical fitness was carried out for three days with the target of football schools in Bangkalan Regency (Prabu FC, Bangkalan Soccer Academy, and Dimensie FC) sequentially. Positive responses can be well received by players, coaches and coaches as if it were football, which means that the solution program for existing problems is able to have a positive impact on partners.